PENGARUH DIGITAL MARKETING TERHADAP PENDAPATAN USAHA MIKRO - Yunia, Noorma; Rohmatulloh, Puri; Albadiah, Ilmi (Universitas La Tansa Mashiro, 2023)
Digital Marketing is a tool as an intermediary for marketing communication which is currently widely used by social media in introducing its products in the modern era. One of them is by using social media as a tool to promote. The problems to be discussed are How Digital Marketing, Micro Business Income and the significant influence between Digital Marketing on business income for micro business actors on Jl. Multatuli, Rangkasbitung District, Lebak Regency. This research is a correlational quantitative research that aims to examine the effect of the independent and dependent variables. This study aims to examine how Digital Marketing, Micro Business Income and the significant influence between Digital Marketing on business income for micro business actors on Jl. Multatuli, Rangkasbitung District, Lebak Regency. This study uses a saturated sampling method. The sample in this study amounted to 52 respondents with samples taken from 2 (two) variables developed. Data collection techniques using a questionnaire with a Likert scale measurement. The data collection method uses a questionnaire method which is then analyzed by simple linear regression analysis with a test (t test) and simultaneous test (F test) with the help of SPSS Statistics 20. It can be seen that micro business income is influenced by Digital Marketing by 0.196 or by 30%, while the remaining 70%, influenced by other factors not examined. Based on the results of the study, that Digital Marketing has a real and positive relationship to micro business income of 3,496. Thus, t count > t table (3,496 > 1,675). So that the significant value <0.05 is 0.001 <0.05, then Ho is rejected and Ha is accepted, which means that there is a partially significant influence between the independent variable, namely Digital Marketing, on the dependent variable, namely Micro Business Income.